Aversive event unpredictability causes stress‐induced hypoalgesia. (29th March 2015) - Quelhas Martins, Amadeu; McIntyre, David; Ring, Christopher
Abstract Temporal predictability, or knowing when a noxious stimulus will occur, has been implicated in stress‐induced hypoalgesia, but the contribution of event predictability, or knowing what the stimulus will be, remains poorly understood. To address this issue, we examined the effects of event predictability on pain intensity ratings and nociceptive flexion reflex responses. Participants repeatedly experienced five intensities of electrocutaneous stimulation, ranging from nonpainful to extremely painful, delivered either randomly (unpredictability group) or blocked (predictability group) with no cues provided. Unpredictable shocks produced the lowest pain ratings while evoking the highest flexion reflex responses. Moreover, anticipatory heart rate data indicated that unpredictable trials were the most physiologically arousing. Our findings show that uncertainty about the upcoming stimulus intensity is stressful and unpleasant, thereby causing hypoalgesia and reflex potentiation.